Analytical hierarchy process and Markov Chain in shared knowledge through social media - Sulaiman, Nor Intan Saniah; Ghazali, Saadiah; Zabidi, Nerda Zura; Omar, Mohd Faizal; Alias, Rose Alinda (Penerbit UTM Press, 2015)
Many studies have been performed to measure successful knowledge sharing in general.However, limited study has been done to assess successful knowledge sharing through social media.Hence, in this paper intend to discuss our approach to assess knowledge sharing among personal social media user.In order to achieve our objective, we proposed to integrate Analytic Hierarchy Process (AHP) and Markov Chain (MC) technique to investigate the pattern of the shared knowledge through social media.Markov Chain will be used to model the knowledge sharing success through expert opinion and stochastic process.We anticipate the outcome of the assessment in a form of a final matrix showing the probability of successful knowledge sharing through social media.The elements in each row of the Markov Chain transition matrix will be calculated using Analytic Hierarchy Process. The assessment tool produce from our research is expected to benefit policy maker or internet user in order to enhance their knowledge sharing strategy in social media application.